Efficacy and Mechanism of Buyang Huanwu Decoction in Patients With Ischemic Heart Failure: A Randomized, Double-Blind, Placebo-Controlled Trial Combined With Proteomic Analysis - Zhu, Mingjun; Wei, Jingjing; Li, Ying; Wang, Yongxia; Ren, Junguo; Li, Bin; Ma, Bo; Wang, Xinlu; Qiao, Lijie; Zhou, Cheng; Liu, Jianxun (Frontiers in Pharmacology, 2022)
Objective: Buyang Huanwu Decoction (BYHW), a famous herbal prescription in traditional Chinese medicine (TCM), has been used for two hundred years for treating ischemic heart failure (IHF). This study aims to assess the efficacy and safety of BYHW combined with guideline-guided pharmacotherapy in patients with IHF and explore the biological mechanism by which BYHW exerts its efficacy. Methods: In the multicenter, double-blind, randomized controlled trial, a total of 80 patients with IHF were randomized to receive BYHW or placebo for three months. The primary efficacy endpoints were New York Heart Association (NYHA) classification, TCM syndrome scores, N-terminal pro-B-type natriuretic peptide (NT-ProBNP), whereas the mechanism exploration endpoints included energy metabolism parameters and coagulation function parameters. In addition, we performed the proteomic study of the serum of patients after treatment by label-free quantification technology to verify the candidate target proteins and pathways. Results: After three months of treatment, the NYHA classification, TCM syndrome scores, and the percentage of subjects with at least 30% reduction in NT-ProBNP were significantly improved in the BYHW group, compared with the control group (P< 0.05); BYHW treatment also significantly regulated blood glucose, blood lipid levels, ameliorated energy metabolism and improved coagulation function parameters. There were no significant differences in safety endpoints between the two groups. In addition, we obtained 56 differentially expressed proteins by proteomics, including 20 up-regulated proteins and 36 down-regulated proteins. Bioinformatic analysis revealed the mechanism of BYHW treatment was significantly related to complement and coagulation cascades, cholesterol metabolism, NF-kappa B signaling pathway, PI3K-Akt signaling pathway, and metabolic pathways. Among these differentially regulated proteins, fibrinogen gamma (FGG), fibrinogen beta (FGB), Carboxypeptidase B2 (CPB2), Coagulation factor XIII A (F13A1), Intercellular adhesion molecule1 (ICAM1), Apolipoprotein C-II(APOC2), Apolipoprotein C-I(APOC1), and CD44 were found to be signature proteins associated with the efficacy of BYHW against IHF. Conclusion: BYHW treatment can further improve cardiac dysfunction and clinical symptoms in IHF based on standard therapy without apparent adverse effects. Additionally, BYHW may play a therapeutic role in IHF by improving energy metabolism and regulating coagulation function through multiple targets and pathways.